1981
DOI: 10.1172/jci110022
|View full text |Cite
|
Sign up to set email alerts
|

Continuous Negative External Chest Pressure Decreases Transvascular Lung Water Transport in Sheep after Pseudomonas Bacteremia

Abstract: A B S T R A C T We studied the effects of continuous negative external chest pressure (CNECP) produced by a cuirass appliance on lung water and protein transport in sheep with chronic lung lymphatic fistulas. We compared data obtained during periods of mechanical ventilation (base line) to period of CNECP, using identical ventilatory support. Three groups were studied: six sheep were studied before and after application of CNECP for 1 h (control) and again after induction of a pulmonary vascular permeability d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

1991
1991
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 43 publications
0
6
0
Order By: Relevance
“…Also, abdominal CENP may more effectively dislocate the diaphragm [10], resulting in more pronounced effects on pleural pressures. The dislocation of the diaphragm increased end-expiratory lung volume (EELV) in a bacterial infection model in sheep [26]. Although EELV was not assessed in our study, the results of the gas exchange suggest an increase EELV comparable to that resulting from PEEP alone.…”
Section: Discussionmentioning
confidence: 52%
See 1 more Smart Citation
“…Also, abdominal CENP may more effectively dislocate the diaphragm [10], resulting in more pronounced effects on pleural pressures. The dislocation of the diaphragm increased end-expiratory lung volume (EELV) in a bacterial infection model in sheep [26]. Although EELV was not assessed in our study, the results of the gas exchange suggest an increase EELV comparable to that resulting from PEEP alone.…”
Section: Discussionmentioning
confidence: 52%
“…In fact, the application of external negative pressure on the abdomen CENP decreased the ventro-dorsal pleural pressure gradient in another experimental study [25]. The vertical gradient of transpulmonary pressure, which is associated with lung collapse in dependent lung regions, is induced by gravitational forces [26]. One hypothesis of applying local negative pressure externally to the thorax is to decrease or even invert this vertical gradient to reduce derecruitment and shift the ventilation towards dependent lung regions.…”
Section: Discussionmentioning
confidence: 98%
“…CNEP has favorable effects on permeability and hydrostatic pulmonary edema [ 6 , 7 ]. In a sheep model inoculated with Pseudomonas bacteria, CNEP decreased hydrostatic filtration pressure and lung lymph flow [ 13 ]. In dogs with pulmonary edema induced by oleic acid, CNEP increased extravascular lung water volume, but did not change central blood volume [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, CNECP has been shown to have an advantage in improving cardiac output compared to PEEP with identical increases in FRC. CNECP has also been shown to decrease pulmonary blood volume, pulmonary arterial pressure, and hydrostatic filtration pressures, thereby decreasing lung lymph flow (Krumpe and Gorin, 1981). However, the more negative pleural and interstitial pressures during CNECP might result in increased filtration of fluid into the lung interstitium, thereby causing pulmonary edema.…”
Section: Negative Pressure Inflationmentioning
confidence: 99%
“…It has been suggested that a significant increase in alveolar surface tension can induce pulmonary edema, even when the capillary oncotic and hydrostatic pressures are normal (Culver and Butler, 1980;Krumpe and Gorin, 1981;Pain and West, 1966). The presence of such edema can, in turn, alter the relationship between the pulmonary arterial and alveolar pressures.…”
Section: Surface Tension Effects On Pulmonary Hemodynamicsmentioning
confidence: 99%